(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article focuses on the trends in the study of environmental security issues in world science and environmental problems have become a global problem in world science. Therefore, not only one or two countries, but also many countries that are thinking about the balance of the world around us, have focused on solving this problem. The environmental crisis and problems that are spreading around the world today mean that it is necessary to treat nature correctly and pay more attention to it. In particular, it was written that solving this problem has risen to the level of state policy in Uzbekistan.